2021
DOI: 10.3897/folmed.63.e69003
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of pneumothorax in patients with COVID-19 – results and management

Abstract: Introduction: The new coronavirus, SARS-CoV-2, provokes infection with different clinical presentation. It involves an asymptomatic condition, mild variants with fever and dry cough to severe pneumonia, adynamia and respiratory failure with lethal outcome. The fibrotic lung tissue after the inflammatory process is a background for development of a secondary pneumothorax. Although it rarely causes lethal outcomes in COVID-19 patients, pneumothorax requires early diagnosis and adequate treatment to prevent any c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(25 reference statements)
0
2
0
Order By: Relevance
“… 25 There are limited medical intervention strategies to prevent the COVID-19. 26 Therefore, the deeper we clarify the pathogenic mechanisms of this disease, the better treatment efficacy will be. Emerging evidence indicated that the multi-organ failures rapidly happened in severe COVID-19 cases may due to the hemoglobin damage which could lead to iron overload.…”
Section: Discussionmentioning
confidence: 99%
“… 25 There are limited medical intervention strategies to prevent the COVID-19. 26 Therefore, the deeper we clarify the pathogenic mechanisms of this disease, the better treatment efficacy will be. Emerging evidence indicated that the multi-organ failures rapidly happened in severe COVID-19 cases may due to the hemoglobin damage which could lead to iron overload.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations are described as acute or chronic: the acute event the patient begins with respiratory stress, febrile syndrome, pleuritic pain in the lower portion of the right hemithorax, irritative cough, yellowish sputum in cases of BBPF, and right pleural effusion. The chronic condition is characterized by chronic cough, occasional yellow sputum, intermittent fever, and pneumonia-like conditions 8,9 .…”
Section: Introductionmentioning
confidence: 99%